Impression cytology and in vivo confocal microscopy in corneas with total limbal stem cell deficiency - Araújo, Aline Lütz de [UNIFESP] (2013)
PURPOSES: To describe corneal changes seen on in vivo confocal microscopy in patients with total limbal stem cell deficiency and to correlate them with cytological findings. METHODS: A prospective case series including 13 eyes (8 patients) with total limbal deficiency was carried out. Stem cell deficiency was diagnosed clinically and by corneal impression cytology. Confocal images of the central cornea were taken with the Heidelberg Retina Tomograph II, Rostock Corneal Module (Heidelberg Engineering, Heidelberg, Germany). RESULTS: Impression cytology of the cornea revealed conjunctival epithelial cells and goblet cells in all cases. In vivo confocal microscopy showed disruption of normal layers of the corneal epithelium in all eyes. Confocal images showed cells with characteristics of conjunctival epithelium at the cornea in 76.9% of the total. These findings on confocal microscopy were compatible to limbal stem cell deficiency. Additionally, goblet cells, squamous metaplasia, inflammatory cells and dendritic cells were observed. The sub-basal nerve plexus was not identified in any of the corneas. Corneal neovessels were observed at the epithelium and stroma. All cases showed diffuse hyper-reflective images of the stroma corresponding to opacity of the tissue. CONCLUSIONS: Limbal stem cell deficiency had been confirmed by impression cytology in all cases, and 76.9% of the cases could also be diagnosed by in vivo confocal microscopy through the conjunctival epithelial cell visualization on the corneal surface. Frequent confocal microscopy findings were abnormal cells at the cornea (conjunctival epithelial, goblet and inflammatory cells), corneal neovessels and diffuse hyper-reflection of the stroma.